Synovial Fluid Lubricant Properties Are Transiently Deficient After Arthroscopic Articular Cartilage Defect Repair With Platelet-Enriched Fibrin Alone and With Mesenchymal Stem Cells. Issue 7 (27th July 2014) - Grissom, Murray J.; Temple-Wong, Michele M.; Adams, Matthew S.; Tom, Matthew; Schumacher, Barbara L.; McIlwraith, C. Wayne; Goodrich, Laurie R.; Chu, Constance R.; Sah, Robert L.
Background: Following various types of naturally occurring traumatic injury to an articular joint, the lubricating ability of synovial fluid is impaired, with a correlated alteration in the concentration and/or structure of lubricant molecules, hyaluronan, and proteoglycan-4 (PRG4). However, the effect of arthroscopic cartilage repair surgery on synovial fluid lubricant function and composition is unknown. Hypothesis: Arthroscopic treatment of full-thickness chondral defects in horses with (1) platelet-enriched fibrin or (2) platelet-enriched fibrin + mesenchymal stem cells leads to equine synovial fluid with impaired lubricant function and hyaluronan and PRG4 composition. Study Design: Controlled laboratory study. Methods: Equine synovial fluid was aspirated from normal joints at a preinjury state (0 days) and at 10 days and 3 months following fibrin or fibrin + mesenchymal stem cell repair of full-thickness chondral defects. Equine synovial fluid samples were analyzed for friction-lowering boundary lubrication of normal articular cartilage (static and kinetic friction coefficients) and concentrations of hyaluronan and PRG4, as well as molecular weight distribution of hyaluronan. Experimental groups deficient in lubrication function were also tested for the ability of exogenous high–molecular weight hyaluronan to restore lubrication function. Results: Lubrication and biochemical data varied with time after surgery but generally not between repair groups. Relative to preinjury, kinetic friction was higher (+94%) at 10 days but returned to baseline levels at 3 months, while static friction was not altered. Correspondingly, hyaluronan concentration was transiently lower (−64%) and shifted toward lower molecular weight forms, while PRG4 concentration was increased (+210%) in 10-day samples relative to preinjury levels. Regression analysis revealed that kinetic friction decreased with increasing total and high–molecular weight hyaluronan. Addition of high–molecular weight hyaluronan to bring 10-day hyaluronan levels to 2.0 mg/mL restored kinetic friction to preinjury levels. Conclusion: Following arthroscopic surgery for cartilage defect repair, synovial fluid lubrication function is transiently impaired, in association with decreased hyaluronan concentration. This functional deficiency in synovial fluid lubrication can be counteracted in vitro by addition of high–molecular weight hyaluronan. Clinical Relevance: Synovial fluid lubrication is deficient shortly after arthroscopic cartilage repair surgery, and supplementation with high–molecular weight hyaluronan may be beneficial.